An Environmental Plan for Mysore, India - Edelman, David J (Advances in Social Sciences Research Journal, 2014)
This paper summarizes the report of a graduate level workshop that took place at the School of Planning, College of Architecture, Art and Planning, University of Cincinnati, USA, the objective of which was to prepare students to work overseas in data-poor environments as professional consulting planners. Several lectures were given to set the framework for the class of eighteen students to operate in sector-level working groups to prepare a 5-year plan to solve the urban environmental problems of Mysore, India, one of Cincinnati’s sister cities, utilizing a real-world data base and a limited budget. This project culminated in the preparation of a professional quality plan. The instructor, who has over thirty years of planning experience in developing countries, including India, attempted to create an atmosphere within the project that duplicates the actual conditions of carrying out such a consultancy.